Detection of Helicobacter pylori antibodies in Patients with Chronic Liver Disease in Iraq - Ali, Najah; Ali, Najah (University of Thi-Qar Journal of Science, 2012)
The study was carried out to determine the prevalence of H. pylori antibodies in patients with chronic liver disease (CLD), by detecting the presence of stool antigen (HpSA), serum, and salivary anti-H. pylori antibody using ELIZA and compared with Rapid Urease test (gold standard). A one hundred and seventy six endoscopy were carried out for patients with or without chronic liver disease. The result indicated that among 130 patients with (CLD), and 46 patients without CLD, the commonest endoscopy diagnosis by gastric biopsy was gastritis (22.72%), duodenal ulcer (17.61%), and Gastric ulcer (11.93%).The serum antibody positivity was higher (83.0%), followed, HpSA (74.4%), salivary antibodypositivity (71.0%) and rapid urease test (RU) positivity (70.6%). In controls salivary antibody and rapidurease test positivity was higher than in CLD patients, while HpSA and serum antibody was higher inCLD patients. On the other hand, it was associated with sex and age. The sensitivity and specificity ofHpSA were 94.6% and 91.6%, respectively.